DECISION MAKING ANALYSIS OF MAINTENANCE STRATEGY TO RESPOND CHF 6 AND CHF 7 OPERATIONS - Wijaya, Gito; Hermawan, Pri (Universitas Nusa Cendana, 2025)
PT Black Energy has infrastructure on both the mining side includes a total of 5 Coal Handling Facility (CHF) systems, and the unloading terminal side includes the Kertapati dock and the Tarahan port. To increase coal transport volume by 2026, adequate infrastructure development is needed by adding more CHF on the mining side and for the unloading terminal side, which will involve adding more unloading terminals. The maintenance department is tasked with maintaining the CHF system. Meanwhile, to carry out its maintenance activities on the existing CHF system, the maintenance department is currently facing an issue with a shortage of supervisors. The maintenance department must develop new strategy to optimize its performance in maintaining the existing 5 CHF systems while also preparing to accommodate the addition of CHF 6 & CHF 7 in 2026. This research was conducted using secondary data from maintenance department documentation studies and primary data through interviews with Subject Matter Expert. Value-Focused Thinking (VFT) method was used to identifying and describing values and objectives that are used as the foundation to generating alternatives and attributes for decision making process. Decision making to select the best alternative was conducted using Simple Multi Attribute Rating Technique (SMART) which will evaluate and compare alternatives with multiple attributes involved while each attribute represents a different aspect or criteria that matters in the decision. The research result show that CHF system focused maintenance model is the best alternative to respond additional CHF 6 & CHF 7 operations in 2026 where each Assistant Manager for mechanical and electrical maintenance division will be responsible for a specific CHF system. This research supports the maintenance department in solving the issue of manpower shortages that will inevitably occur in 2026. Keywords: Decison Making; Value-Focused Thinking (VFT); Simple Multi Attribute Rating; Technique (SMART)